Safety profile and side effects of infliximab and adalimumab in inflammatory bowel disease at a referral center in northeastern Brazil - Santos, Joelma Aurélio de Sousa (2024)
Introduction: Anti-tumor necrosis factor-alpha agents (Anti-TNF-alpha) are an effective treatment option in patients with moderate and severe inflammatory bowel disease (IBD). Objectives: To evaluate safety profile of infliximab (IFX) and adalilumab (ADA) in IBD patients over a 10-year period at a referral center in Northeastern Brazil. Methodology: The medical records of 123 patients, of whom 104 (84.5%) had Crohn’s disease and 19 (15.4%) had ulcerative colitis, were reviewed for side effects associated with the use of IFX (n=83) and ADA (n=40). Results: Thirty-one patients (25%) experienced side effects (IFX n=21; ADA n=10) (p=0.971), 15 (48%) of which were severe (IFX n=10; ADA n=5) (p=0.942). Acute reactions occurred in 9 patients (7.3%), infections in 13 (10%), malignancies in 3 (2,4%), psoriasis in 4 (3,2%), in addition to 3 deaths (2,4%). Conclusion: The frequency of side effects was similar for IFX and ADA. Both drugs are safe in the treatment of IBD, but careful screening and monitoring are necessary to identify and follow patients at risk of severe side effects.